Arabic Language Learning AT MTs Mazro'atul Ulum Paciran Lamongan - Islamiyah, Anisatin; Aimmah, Aisy Wildatil; Saputra, Angga (Yayasan Mutiara Hati Moeslem, 2025)
This study aims to describe and analyze the Arabic language learning process at MTs Mazra'atul Ulum Paciran Lamongan, including the methods used, challenges faced, and efforts made to improve the quality of learning. The background of this study is based on the importance of mastering Arabic as the main language in Islamic studies, especially in Islamic boarding school-based madrasah environments. The research method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. The results of the study indicate that Arabic language learning at MTs Mazra'atul Ulum uses various methods such as qawa'id wa tarjamah, muhadatsah, and mubasyaroh. However, there are several obstacles faced, including low student motivation, limited learning media, and lack of competence of some teachers. To overcome these obstacles, the madrasah has made various efforts such as teacher training, development of learning media, and implementation of more communicative learning methods. This study concludes that Arabic language learning at MTs Mazra'atul Ulum has shown positive developments, but still requires strengthening in terms of pedagogy and supporting facilities so that learning objectives can be achieved optimally.